The people behind the papers - Jingjing Sun and Angelike Stathopoulos. - Anonymous, (Development, 2024)
Collective migration of caudal visceral mesoderm (CVM) cells in Drosophila embryos helps form the longitudinal muscles of the larval gut. In their study, Angelike Stathopoulos and colleagues reveal that cell division coordinates two gene expression programmes in migrating CVM cells. To know more about their work, we spoke to the first author, Jingjing Sun, and the corresponding author, Angelike Stathopoulos, Professor in the Division of Biology at the California Institute of Technology, USA.